2015
DOI: 10.1155/2015/507018
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Evaluation of Field Application of High-Fluidity Concrete Containing High Volume Fly Ash

Abstract: In the recent concrete industry, high-fluidity concrete is being widely used for the pouring of dense reinforced concrete. Normally, in the case of high-fluidity concrete, it includes high binder contents, so it is necessary to replace part of the cement through admixtures such as fly ash to procure economic feasibility and durability. This study shows the mechanical properties and field applicability of high-fluidity concrete using mass of fly ash as alternative materials of cement. The high-fluidity concrete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The mortar with high fly ash content (replacing up to 80% of fly ash) that meets the minimum compressive strength at an early age (R3 ≥ 13MPa, 3 days old) and (R28 ≥ 40MPa, 28 days old) will make an important contribution in sustainable development, reducing CO2 emissions by replacing Portland cement with fly ash, saving natural resources, and limiting environmental pollution on the impact of thermal power coal ash and construction industry using Portland cement. Moreover, with such required strength, it is suitable for the actual construction of civil works, or prefabricated components that need to be demoulded early and is equivalent to commercial products with the same compressive strength [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The mortar with high fly ash content (replacing up to 80% of fly ash) that meets the minimum compressive strength at an early age (R3 ≥ 13MPa, 3 days old) and (R28 ≥ 40MPa, 28 days old) will make an important contribution in sustainable development, reducing CO2 emissions by replacing Portland cement with fly ash, saving natural resources, and limiting environmental pollution on the impact of thermal power coal ash and construction industry using Portland cement. Moreover, with such required strength, it is suitable for the actual construction of civil works, or prefabricated components that need to be demoulded early and is equivalent to commercial products with the same compressive strength [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The aim is to accelerate the hydration of both fly ash and cement and enhance the positive effects of fly ash on the refinement of pores and improvements in the microstructure and interfacial transition zones [29,31]. A study by Choi et al [32] indicated that by admixing superplasticizer and an air-entraining agent with a decreased water dosage and increased content of binders, a high-fluidity concrete with 50% fly ash content ensured early strength and reached the target strength at a curing age of 28 days. Yu et al [33] reported that by lowering the water-to-binder ratio and properly combining raw materials, concrete with 40-70% fly ash content had adequate strength and workability, and the mechanical properties could be improved by admixing a small amount of silica fume.…”
Section: Introductionmentioning
confidence: 99%
“…Fly ash is a by-product of coal combustion in power stations, which presents as tiny grains with a certain pozzolanic activity. As one of the industrial solid wastes, fly ash has attracted much more attention on its comprehensive utilization to protect the environment (Wu and Lian, 1999;Choi et al, 2015;Amran et al, 2021). Based on its chemical composition, grain fineness, and pozzolanic activity, fly ash is classified into different types and is most widely used as a mineral admixture of cement and concrete (Wu and Lian, 1999;Li et al, 2013;GB/T1596-2017GB/T1596- , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve economic benefits from effective utilization of fly ash, studies have been done to improve the applicability of FAC with large content of fly ash. With the replacement of 50% cement by fly ash containing 6.49% calcium oxide, the high-fluidity FAC was made by admixing the superplasticizer and air-entraining agent; the early strength was ensured by decreasing the water dosage and increasing the content of binders, and then the strength at the curing age of 28 days reached the target (Choi et al, 2015). In case of the replacement of 20%-80% cement by fly ash, the flowability of fly ash cement composites is improved at paste and concrete level (Thiyagarajan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%